Destructive and non-destructive testing of the performance of copper slag fiber-reinforced concrete - Chakrawarthi, Vijayaprabha; Dharmar, Brindha; Avudaiappan, Siva; Amran, Mugahed; Flores, Erick Saavedra; Alam, Mohammad Ayaz; Fediuk, Roman; Vatin, Nikolai Ivanovicn; M. Rashid, Raizal S. (MDPI, 2022)
Concrete technology is adopted worldwide in construction due to its effectiveness, performance, and price benefits. Subsequently, it needs to be an eco-friendly, sustainable, and energy-efficient material. This is achieved by replacing or adding energy-efficient concrete materials from industries, such as ground granulated blast furnace slag, steel slag, fly ash, bottom ash, rice husk ash, etc. Likewise, copper slag is a waste material produced as molten slag from the copper industry, which can be used in concrete production. Copper slag can perform roles similar to pozzolans in the hydration process. This paper extends the comparative study of copper slag concrete with polypropylene fiber (PPF) subjected to destructive and non-destructive testing. Under destructive testing, compressive strength of concrete cubes, compressive strength of mortar cubes, splitting tensile tests on cylindrical specimens, and flexural tests on plain cement concrete were conducted and analysed. Ultrasonic pulse velocity and rebound hammer tests were performed on the samples as per IS13311-Part 1-1992 for non-destructive testing. The 100% replacement of copper slag exhibited a very high workability of 105 mm, while the addition of 0.8% PPF decreased the flowability of the concrete. Hence, the workability of concrete decreases as the fiber content increases. The density of the concrete was found to be increased in the range of 5% to 10%. Furthermore, it was found that, for all volume fractions of fiber, there was no reduction in compressive strength of up to 80% of copper slag concrete compared to control concrete. The 40% copper slag concrete was the best mix proportion for increasing compressive strength. However, for cement mortar applications, 80% copper slag is recommended. The findings of non-destructive testing show that, except for 100% copper slag, all mixes were of good quality compared to other mixes. Linear relationships were developed to predict compressive strength from UPV and rebound hammer test values. This relationship shows better prediction among dependent and independent values. It is concluded that copper slag has a pozzolanic composition, and is compatible with PPF, resulting in good mechanical characteristics.